2015
DOI: 10.1017/ipm.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Increased use of security personnel in Irish psychiatric hospitals: 2008–2012

Abstract: Activity of security personnel in psychiatric hospitals may not be role appropriate, compliant with legislation or conducive to treatment. Best practice guidelines should be developed in consultation with multiple stakeholders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In a review of the literature on violence in the ED setting, research reported around 50% of EDs had security personnel present, with security provisions in the United States (US) generally reported as greater than in the United Kingdom (UK) (Stirling, Higgins, & Cooke, 2001). A more recent study in the UK reported an increase in the use of security personnel in Irish psychiatric hospitals between 2008 and 2012 (Shannon, Devitt, & Murphy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of the literature on violence in the ED setting, research reported around 50% of EDs had security personnel present, with security provisions in the United States (US) generally reported as greater than in the United Kingdom (UK) (Stirling, Higgins, & Cooke, 2001). A more recent study in the UK reported an increase in the use of security personnel in Irish psychiatric hospitals between 2008 and 2012 (Shannon, Devitt, & Murphy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many healthcare facilities employ security guards as part of their security strategy 1. Adeniyi and Puzi2 attribute this to violent and aggressive behaviours that are not uncommon in many healthcare institutions, including hospitals and psychiatric and emergency units 3–6. Such behaviours are among the key reasons for the employment of security guards 7.…”
Section: Introductionmentioning
confidence: 99%